Elytra-inspired zirconium phosphate nanonetwork: Toward high-quality osseointegration and physical-chemical-mechanical bond at the interface for zirconia-based dental materials - Shuyi Wu; Yingyue Sun; Qihong Zhang; Wen Si; Peng Gao; Lei Lu; Zhennan Deng; Lihua Xu; Xinkun Shen; Jinsong Liu (Bioactive Materials)
Yttria-stabilized zirconia (YSZ) is widely used in dental implants and prostheses due to its excellent aesthetic and restorative properties. However, its bio-inert surface limits early osseointegration and weakens bonding strengths with porcelain veneer/resin cement. Inspired by the structure of beetle elytra, this work proposes a novel strategy involving a self-assembled trabecular-honeycomb biomimetic zirconium phosphate (ZrP) nanonetwork to modify YSZ surfaces. This approach simultaneously enhances energy dissipation, interfacial bonding, and osseointegration. The pore size of ZrP nanonetwork was precisely controlled by adjusting reaction temperatures (120 °C and 160 °C) and phosphoric acid concentrations (1.0 wt% and 2.5 wt%). Compared to conventional YSZ, the ZrP nanonetworks achieved remarkable improvements in bond strength, showing increases of 111 % with porcelain veneer and 336 % with resin cement. These enhancements are attributed to multiscale physical-chemical-mechanical interactions, including micromechanical anchoring, chemical bonding via phosphate groups, and energy dissipation through topological optimization. In vitro studies demonstrated that large-pore-size nanonetworks promote osteogenic differentiation of osteoblasts and modulate macrophage polarization toward the M2 phenotype, fostering an immune environment conducive to bone regeneration. In vivo experiments further validated the superior osseointegration and bone regeneration capacities of the large-pore-size ZrP nanonetwork. Collectively, this biomimetic ZrP nanonetwork-modified YSZ, with its exceptional physical-chemical-mechanical bonding properties, osseointegration potential, and immune-modulating capabilities, represents a groundbreaking advancement in zirconia-based material for dental implants and prostheses.